Response and prognosis after neoadjuvant chemotherapy in 1,051 patients with infiltrating lobular breast carcinoma - Loibl, Sibylle; Volz, Cristina; Mau, Christine; Blohmer, Jens-Uwe; Costa, Serban D.; Eidtmann, Holger; Fasching, Peter; Gerber, Bernd; Hanusch, Claus; Jackisch, Christian; Kuemmel, Sherko; Huober, Jens; et al. (Breast Cancer Research and Treatment, 2014)
Invasive lobular carcinomas (ILC) show better clinical behaviour compared with other histological types, but significantly lower pathological complete response (pCR) rates after neoadjuvant chemotherapy (NACT). We investigated whether factors influencing pCR rate in ILC after NACT can be identified and whether clinical outcome is different. 9,020 breast cancer patients from nine German neoadjuvant trials with known histological type were pooled. 11.7 % of tumours were ILC. Endpoints were: pCR rate, surgery type and survival. ILC was associated with older age, larger tumour size, lymph node negativity, lower grade and positive hormone-receptor-status (HR). Patients with ILC achieved a significantly lower pCR rate compared with non-ILC patients (6.2 vs. 17.4 %, P < 0.001). The pCR rate was 4.2 % in ILC/HR+/G1-2, 7.0 % in ILC with either HR- or G3, and 17.8 % in ILC/HR-/G3. Mastectomy rate was higher in ILC compared with non-ILC patients irrespective of response to NACT (pCR: 27.4 vs. 16.6 %, P = 0.037 and non-pCR: 41.8 % vs. 31.5 %, P < 0.0001). Age and HR independently predicted pCR in ILC. In ILC patients, pCR did not predict distant disease free (DDFS) and loco-regional disease free survival (LRFS), but overall survival (OS). Non-pCR patients with ILC had significantly better DDFS (P = 0.018), LRFS (P < 0.0001) and OS (P = 0.044) compared with non-ILC patients. Patients with ILC had a low chance of obtaining a pCR and this is not well correlated with further outcome. The mastectomy rate was considerably high in ILC patients even after obtaining a pCR. We, therefore, suggest to offer NACT mainly to ILC patients with HR-negative tumours.
EVALuna2:17507